ANALISIS BAURAN PEMASARAN (MARKETING MIX ) TERHADAP PRODUK TABUNGAN DALAM MENINGKATKAN JUMLAH NASABAH - Astuti, Nurwidya Fatohona; Supardi, Supardi; Shar, Aan (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
The purpose of this research is to find out what the savings products at BPRS Fadhilah are, to find out the prices of savings products at BPRS, to find out what the location of BPRS Fadhilah is, to find out what promotions are carried out by BPRS Fadhilah. This research is field research, using a qualitative descriptive approach. The data analysis technique used is data reduction, data presentation and drawing conclusions. This research data collection used observation, interview and documentation techniques. The research results show that the products available at BPRS Fadhilah are of high quality and have advantages such as implementing a cash pickup service pattern with customers who use savings products. And the prices of savings products at BPRS Fadhilah are very affordable and in line with the quality and benefits of savings products with no administration costs. On the other hand, BPRS Fadhilah is located on Jl. A. Yani, District. Tlk Segara, Bengkulu City, Bengkulu 38119. This location is very strategic, and the promotions carried out by BPRS Fadhilah are direct and indirect promotions. And the media used by BPRS Fadhilah in marketing savings products are Instagram, Facebook, YouTube. It can be concluded that BPRS Fadhilah's savings products are currently good and of good quality at affordable prices and in accordance with the benefits of the savings products, and the place/location of BPRS Fadhilah is very strategic and has a comfortable office, finally there are two promotions carried out by BPRS Fadhilah, namely promotions directly and indirectly.